Google classroom for emergency remote learning: the students’ perceptions - Eka Wulandari; Yuyun Putri Mandasari (STAI Hubbulwathan Duri, 2023)
This study aimed at finding out college students’ point of view on the use of Google Classroom for Emergency Remote Learning during COVID-19 outbreak. A survey research design was employed by the researcher for this research. The respondents were 209 students of Poltekkes Kemenkes Malang, Indonesia, coming from various departments, namely: nursing, midwifery, occupational health and safety, and blood bank technology. The online questionnaire consisted of 31 items was distributed to the respondents as the research instrument to collect the primary data. Once all the data were collected, then they were explained in descriptive manner, tabulated, and analyzed. The results showed that the students of Poltekkes Kemenkes Malang got positive perspectives on the use of Google Classroom in all aspects during the emergency online learning and only a very small percentage of students (below 10%) showed negative response regarding the use of Google Classroom. According to them, Google Classroom did not help them mastering the English materials and improving their achievement. Based on the findings it can be concluded that Google Classroom for ermergency remote learning gained positive perceptions from the students but there are still few constraints dealing with the use of Google Classroom for emergency remote learning, so the teachers need to evaluate the utilization of this platform to get more benefits and minimize the drawbacks, particularly for ESP context.